STUDI EKSPLORASI PALMISTRY DAN FINGER PRINT SEBAGAI GAMBARAN INDIVIDUAL PERSONALITY DALAM POLA ENTREPRENEURIAL DECISION MAKING - Malikah Luqiana Varini; Hafiz Rahman; Rahmi Fahmy (Halu Oleo University, 2025)
This research explores how individual entrepreneurs' personalities can be mapped through palmistry and fingerprint analysis to understand their decision-making patterns. Using an exploratory qualitative approach, this study identifies the linkages between these biometric characteristics and decision-making methods, such as effectuation and causality. The results show that certain patterns in palmistry, such as hand types (fire, earth, air, and water) and life lines, and fingerprints, such as loop, arch, and whorl patterns, provide significant insights into entrepreneurs' personalities. For example, fire hand types reflect courage and creativity, which encourage innovative decisions, while earth hand types are more conservative, favouring stability and planning. The fingerprint patterns also provide additional insights into the personality dimensions that influence how entrepreneurs deal with business challenges.